Surviving Colorectal Cancer: More Than Treatment - Xavier, Belsiyal C. (Indian Journal of Medical and Paediatric Oncology, 2023)
The main aim of this article is to contribute to a complete patient perspective on the psychosocial impact of colorectal cancer. The details included patient personal experience of being a colorectal cancer survivor and perception regarding psychosocial support during management of the illness. Health professionals should assume that patients may have difficulty in illness management and should encourage a discussion of patients' concerns.
Keywords: colorectal cancer; emotional distress; personal experience; psychosocial support